Cardiovascular Disease, Hypogonadism and Erectile Dysfunction: Early Detection, Prevention and the Positive Effects of Long-Term Testosterone Treatment: Prospective Observational, Real-Life Data - Alwani M (Vascular Health and Risk Management, 2021)
Mustafa Alwani,1,2 Aksam Yassin,2– 4 Raidh Talib,2 Ahmad Al-Qudimat,2 Omar Aboumarzouk,2 Raed M Al-Zoubi,2,5 Farid Saad,6 Karim S Haider,7 Abdulla Al Ansari2 1Jordan University of Science and Technology, School of Medicine, Irbid, Jordan; 2Hamad Medical Corporation, Department of Surgery, Division of Urology/Andrology and Section of Surgical Research, Doha, Qatar; 3Weill Cornell Medical College, New York, NY, USA; 4Weill Cornell Medical College, Doha, Qatar; 5Jordan University of Science and Technology, Department of Chemistry, Irbid, Jordan; 6Dresden International University, Center of Medicine and Health Sciences, Dresden, Germany; 7Klinikum Bremen-Mitte, Department of Urology, Bremen, GermanyCorrespondence: Aksam Yassin Rathausallee 94 A, Norderstedt-Hamburg, 22846, GermanyTel +49 40 526 21 57Fax +49 40 526 28 20Email yassin@t-online.dePurpose: Erectile dysfunction (ED) is associated with testosterone deficiency and is a symptom of functional hypogonadism. A correlation between ED and cardiovascular disease (CVD) has been recognized, and ED has been proposed as an early marker of CVD. However, the relationship between ED and CVD risk in hypogonadism requires clarification and whether testosterone therapy (TTh) can be a beneficial treatment strategy, but long-term data are limited. This study investigates long-term TTh in men with hypogonadism and ED with a history of CVD.Methods: Seventy-seven patients with a history of CVD and diagnosed with functional hypogonadism and erectile dysfunction (erectile function domain score < 21 on the International Index of Erectile Function questionnaire (IIEF questions 1– 5)) were enrolled and TTh effects on anthropometric and metabolic parameters investigated for a maximum duration of 12 years. All men received long-acting injections of testosterone undecanoate at 3-monthly intervals. Eight-year data were analysed. Data collection registry started in November 2004 till January 2015.Results: In hypogonadal men receiving TTh, IIEF increased by 5.4 (p< 0.001). Total weight loss was 23.6 ± 0.6 kg after 8 years. HbA1c had declined by an average of 2.0% (P< 0.0001). Total cholesterol levels significantly declined following TTh after only 1 year (P< 0.0001), and HDL increased from 1.6± 0.5 at baseline to 2± 0.5 mmol/L following 8 years of TTh (P< 0.0001). SBP decreased from 164± 14 at baseline to 133± 9 mmHg, signifying a reduction of 33± 1 mmHg (P< 0.0001).Conclusion: In hypogonadal men with a history of CVD, TTh improves and preserves erectile function over prolonged periods with concurrent sustained improvements in cardiometabolic risk factors. Measuring ED and testosterone status may serve as an important male health indicator predicting subsequent CVD-related events and mortality and TTh may be an effective add-on treatment in secondary prevention of cardiovascular events in hypogonadal men with a history of CVD.Keywords: functional hypogonadism, testosterone therapy, erectile function, cardiovascular disease